Nilai Pendidikan dalam Upacara Nyambleh di Pura Pererepan Banjar Denjalan Desa Batubulan Kecamatan Sukawati Kabupaten Gianyar - I Nyoman Alit Supandi (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
The nyambleh ceremony, including the bhutayad ceremony, is realized in the Nyambleh ceremony. Hindus in their daily practice of life are always colored by the Yajna ceremony, as a form of gratitude to Ida Sang Hyang Widhi Wasa, for all the blessings and graces that have been bestowed on mankind on earth. This nyambeleh ceremony must be done and has a uniqueness that can be used as one of the writings. In general, this study aims to find out what the educational value of the Nyambleh ceremony is at Pererepan Temple, Batubulan Village, Sukawati District, Gianyar Regency. In connection with the above, the nyambleh ceremony is very interesting to study. Based on the background of the problem above, the problems can be formulated, namely: 1. The educational value contained in the Nyambleh ceremony at the Pererepan Banjar Temple, Denjalan, Batubulan Village, Sukawati District, Gianyar Regency. The results of the educational value contained in the Nyambleh ceremony at the Pererepan Temple in Batubulan Village, there are four, namely 1. The value of tattwa education referred to in the nyambleh ceremony is the community's belief in Ida Sang Hyang Widhi Wasa. 2. The value of this religious education is found in the community accompanying the Hermitage or Sesuunan after that the Nunas Pinget community and the community continue to carry out the nyambleh ceremony. 3. The value of ethical education contained in the nyambleh ceremony is that the community carries out the teachings of tri Kaya parisuda, how to have good thoughts, good words, and good deeds in community activities and in the implementation of the nyambleh ceremony. 4. While the aesthetic value contained in the nyambleh ceremony when the procession took place was how the colorful banners, very beautiful barong, besides that there was the art of kidung sound and the art of kerawitan and gambelan beleganjur.